Initial clinical evaluation of a non‐contrast‐enhanced MR angiography method in the distal lower extremities. Issue 6 (25th February 2013) - Priest, Andrew Nicholas; Joubert, Ilse; Winterbottom, Andrew Philip; See, Teik Choon; Graves, Martin John; Lomas, David John
<x xml:space="preserve">Abstract</x> Purpose To report the initial experience and diagnostic performance applying a novel flow‐dependent non‐contrast‐enhanced MR angiography (NCE‐MRA) method, in patients with suspected peripheral vascular disease, in comparison with established contrast‐enhanced MRA (CE‐MRA). Methods The lower legs of 34 patients were imaged at 1.5 T with both NCE‐MRA and CE‐MRA. The NCE‐MRA method consisted of a cardiac‐gated balanced‐SSFP sequence with controllable flow‐suppression preparation. Flow‐suppressed and unsuppressed datasets were subtracted to obtain angiograms. Two experienced radiologists assessed both NCE‐MRA and CE‐MRA images, first independently and then in consensus to resolve significant disagreements. Signal loss, vessel conspicuity, vascular disease, venous contamination, artifacts, and diagnostic confidence were assessed. Results Using the CE‐MRA as the "gold standard, " the per‐segment sensitivity and specificity for detection of significant disease were 81.7% and 90.9%, respectively. Mean diagnostic confidence (scale 0–4) was 3.4 for NCE‐MRA and 3.9 for CE‐MRA. Most vessel segments were well visualized but the popliteal arteries often suffered some technique‐related signal loss. Conclusions The NCE‐MRA method was able to visualize most vessel segments with good or excellent confidence, few artifacts, and excellent background suppression, giving moderate agreement with CE‐MRA. However, some segments were poorly visualized, probably due to flow profile distortion in these patients. Magn Reson Med 70:1644–1652, 2013. © 2013 Wiley Periodicals, Inc.